If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -8 = 10 + 4x Reorder the terms: -8 + 7x = 10 + 4x Solving -8 + 7x = 10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + 7x + -4x = 10 + 4x + -4x Combine like terms: 7x + -4x = 3x -8 + 3x = 10 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + 3x = 10 + 0 -8 + 3x = 10 Add '8' to each side of the equation. -8 + 8 + 3x = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = 10 + 8 3x = 10 + 8 Combine like terms: 10 + 8 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| [3x-2]=10 | | 4w^2+9w=5 | | 7n+5-3n=3(n+2) | | (-6y-9z)(-2)= | | 3x^2-10x-25= | | 4(2c)=11c-33 | | -40+8k=-(k-1)+4 | | 513=825-24x | | 10d-6=4d-3d | | 8t-6(2t-1)= | | 0.10x+15.00=0.15x+10.00 | | -10x+22x= | | 4(x-3)-x=0 | | 82-8x=34 | | H=3st | | 2x+1+12x-4=61 | | [2x+1]=7 | | 3x-6=6x+14 | | 9(3x-1)-26x=2 | | 8x-3+5x-4=79 | | [x]=0 | | 2y-6=7y-26 | | 25-2x=3x+15 | | -10x^2+2x+3=0 | | -3b+4b=-8 | | b/4=13 | | (3m+4)-(2m^2-6m+5)= | | 2x^2=x^4-2x^2 | | (3x-4)=54 | | 3+2+x+2+x+2+3=13.5 | | Z^2-3=54 | | 13a-31=2s-9 |